Public disclosure of surgeon's results – pituitary surgery. (June 2014) - Phillips, Nick; Tyagi, Atul; Marks, Paul; Nix, Paul
Abstract Objective. There are few agreed quantifiable outcome measures in pituitary surgery. The goal of this study is to present the measurement of resection volume after surgery for pituitary tumours as a surgeon-specific outcome measure that may have use in illustrating the performance of individual surgeons internally and externally, and contribute to quality improvement in pituitary surgery. Method. The authors used an existing validated method to measure the volume of pituitary tumours. This method was used to retrospectively assess the extent of resection (EOR) in all patients undergoing pituitary surgery for tumour volume reduction over a 3-year period in Leeds, UK. Three surgeons and two techniques (endonasal transsphenoidal surgery and conventional microscopic surgery) were compared. The results are summarised using Funnel plot methodology. Results. The overall mean EOR for the 3 years of study was 54%. There was no difference between endoscopic and microscopic techniques in terms of EOR. Significant differences were found between surgeons' case mix (as estimated by preoperative tumour size) and EOR. One surgeon had smaller tumour cases at operation than the other two surgeons (p = 0.004). One surgeon achieved larger resections than the two other surgeons (p = 0.038 and 0.005). Conclusions. Measuring pituitary volumes manually using segmentation methods and existing software is possible for surgeons and provides valuable information on individual surgeon performance and departmental practice. A simple retrospective review of 3 years of practice has demonstrated that surgeons have different case-mix and their EOR can vary within safe limits. During a period of transition when we changed personnel and technique, the EOR was little affected and this was reassuring from a governance perspective. Performance assessment for low-volume conditions is possible .